The Impact of Green Tax Policy, Environmental Awareness and Religiosity on The Intention of Umkm to Adopt Circular Economy Practices Moderated by Monetary Value - Maulana, Gilang Wirawan Wasis Tirta (Bulletin of Islamic Economics, 2024)
This study aims to determine the effect of green tax policy, environmental awareness, religiosity and monetary value on the intention of MSMEs to adopt a circular economy system. The sampling technique used is purposive sampling, with a total of 120 samples determined using the G-power application. The data analysis method in this study uses partial least squares structural equation modeling (SEM-PLS). The results of the analysis show that the variables of green tax policy, religiosity and monetary value are proven to have a significant influence on the intention of MSMEs. However, the religiosity variable shows a negative value, so it is considered that the higher the value of one's religiosity, the lower the intention, while the environmental awareness variable is proven to have no significant influence on the intention of MSMEs. Meanwhile, the monetary value variable proved unable to moderate the green tax policy variable, environmental awareness and religiosity on MSME intentions.